EFFECTIVENESS OF THE INTERNATIONAL CRIMINAL COURT’S JURISDICTION IN IMPUNITY PREVENTION - Mega Jaya, Belardo Prasetya; Anditya, Ariesta Wibisono (Justitia et Pax, 2020)
This research aims to describe and explain the International Criminal Court’s jurisdictions in an effort to prevent impunity. Additionally, this research provides answer to the question of ICC’s effectiveness in upholding justice over international crimes. This research is a normative law research. The research results shows, under Rome Statute of the International Criminal Court 1998, the purpose of a trial is to end impunity over serious crimes. To implement such a purpose, ICC exercise their jurisdictions conform to Rome Statute. However, the exercise of ICC’s jurisdictions are still ineffective, such phenonemon could arise by many factors.